Communication and medical errors: a bibliometric analysis of research trends and knowledge structures - Birgit Hladschik-Kermer; Olena Litvinova; Gernot Gerger; Michał Ławiński; Maima Matin; Maria Kletecka-Pulker; Eva Hollmann; Alina Volkmar; Magdalena Eitenberger; Atanas G. Atanasov; Thomas Wochele-Thoma (Frontiers in Medicine, 2026)
Background Communication is increasingly positioned in patient safety research as a cross-cutting domain influencing multiple care processes. However, its structural organization within the scientific literature remains insufficiently integrated. Objective This study aims to conduct a large-scale bibliometric analysis of the scientific field linking communication and medical errors and to propose a conceptual communication governance framework integrating the identified communication domains into a coherent structure relevant to healthcare, including nursing practice. Methods We conducted a bibliometric analysis of 13,431 publications indexed in the Web of Science Core Collection (search date: 21 February 2026). Publication trends, thematic evolution, keyword co-occurrence, and international collaboration networks were analyzed using Web of Science analytical tools, the bibliometrix R package, and VOSviewer. To ensure robustness, results were cross-validated with an equivalent Scopus dataset. Results Publication activity increased exponentially after 2000, exceeding 1,000 publications annually after 2020. Four developmental phases were identified: clinical-descriptive (1964–1999), systemic patient safety (2000–2010), team- and patient-centered (2011–2019), and digital and hybrid communication (2020–2026). Five major thematic clusters emerged: pharmacotherapy safety, teamwork and human factors, information transfer and patient-centered communication, digital infrastructure, and organizational safety culture. The United States, England, and Australia dominated scientific output, with contributions from 139 countries/regions overall. Communication is embedded in multiple patient safety areas across the knowledge network. Cross-database analysis established strong temporal consistency between the Web of Science and Scopus datasets (r = 0.985), with consistent bibliometric patterns across both databases, indicating a stable intellectual structure of the field. Conclusion The findings suggest that communication is consistently conceptualized in the literature as a multilevel governance domain within patient safety systems. The proposed conceptual communication governance framework provides a structured basis for refining empirical data, developing clinical risk indicators, and conducting safety research involving nurses.